EFFICACY OF DEXAMETHASONE ALONE COMPARED TO DEXAMETHASONE AND METOCLOPRAMIDE COMBINED FOR POST-OPERATIVE NAUSEA AND VOMITING IN PATIENTS UNDERGOING ABDOMINAL SURGERY - KHALID , M; ASHFAQ , MA; OBAID , A; JAVED , HM; IQBAL , A; BUTT , MR (Biological and Clinical Sciences Research Journal, 2023)
Post-operative nausea and vomiting (PONV) are common complications in patients undergoing major abdominal surgery, with reported frequencies of up to 54% for vomiting and 71% for nausea. PONV, typically within the first 24 hours after surgery, can result in significant morbidity, unexpected hospital admissions, reduced patient comfort, prolonged hospital stays, and increased healthcare costs. The aim of this institutional-based randomized controlled study, conducted at Aziz Bhatti Teaching Hospital in Gujarat from March 2022 to March 2023, was to assess the efficacy of dexamethasone alone and in combination with metoclopramide in preventing post-operative nausea and vomiting in patients undergoing abdominal surgery. One hundred fifty patients aged 18 to 65 who were scheduled for abdominal surgeries were recruited for this study. The patients were randomly assigned to three treatment groups: Group P (placebo), Group D (dexamethasone), and Group DM (dexamethasone and metoclopramide). Data analysis was performed using SPSS version 21, with the one-way ANOVA test used for continuous variables and the Chi-Square test employed for categorical data. A p-value of less than 0.05 was considered statistically significant. The results revealed that the overall incidence of PONV was 62% in the placebo group, 26% in the dexamethasone group, and 14% in the dexamethasone plus metoclopramide group. Significantly fewer patients in the dexamethasone + metoclopramide group (p < 0.05 compared to Group P) and only one patient in the dexamethasone group (p < 0.05 compared to Group P) required rescue antiemetic medication, whereas 8 patients in the placebo group required such treatment. Pain scores, time to first analgesic request, and adverse effects were comparable across all treatment groups. In conclusion, the combination of dexamethasone and metoclopramide demonstrated superior efficacy in preventing PONV compared to dexamethasone alone.